Promoting Wellness for Architecture and Landscape Architecture Students: Lessons Learned from a Mixed Method Study - Dina Battisto; Sallie Hambright-Belue; Lara Browning; Luke Hall; Julia Blouin; Jiaying Dong; Xiaowei Li; Kristian Baber (Building Healthy Academic Communities Journal, 2024)
Background: Universities face increasing pressure to model healthy campuses in response to the ongoing mental health crisis, yet limited research explores ways to improve student wellness.